Integrated 240-GHz Dielectric Sensor With dc Readout Circuit in a 130-nm SiGe BiCMOS Technology - Defu Wang, Klaus Schmalz, Mohamed Hussein Eissa, Johannes Borngräber, Maciej Kucharski, Mohamed Elkhouly, Minsu Ko, Herman Jalli (IEEE Transactions on Microwave Theory and Techniques, 2018)
This paper presents a high-integration miniaturized dielectric spectroscopy system for sensing the change of permittivity at 240 GHz in the SiGe BiCMOS technology. The sensor features a transducer with a resonator to perform bandpass frequency response, whose complex value of S21 is varied with the permittivity of the sample under test. This variation can be detected and recorded as the change of amplitude and phase of the 240-GHz in-phase and quadrature direct conversion mixer. An external 30-GHz source is employed with cascade frequency multiplier chain to deliver a signal through the system with a wide tuning range of 215–245 GHz. An additional probe is employed to carry the sample and implement chip measurements on the probe station. The sensing function of this system is performed with the leaded wire as a metallic sample to be placed on the top of the transducer. Based on the measured dc output voltage changes, the calculated magnitude and phase of IQ signal in the 215–245-GHz range are used to estimate the complex permittivity change of MUTs. This dielectric spectroscopy system is also suitable for sensing the complexy permittivity change at higher frequencies in the future terahertz Lab-on-Chip measurements.